Substance use in patients with sexually transmitted infections: results from a national U.S. survey. - Tetrault, Jeanette M; Fiellin, David A; Niccolai, Linda M; Sullivan, Lynn E (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2010)
Little is known about the prevalence and correlates of substance use in patients diagnosed with sexually transmitted infections (STIs) in the general population. We examined the relationship between STIs and substance use. Of the 54,623 respondents, 1%  reported a past-year STI. STI was associated with alcohol abuse/dependence (AOR 1.8, 95% CI 1.1-3.3), and marijuana use (AOR 2.0, 95% CI 1.4-3.0); but not with past-year alcohol use, cocaine use, nonmedical use of prescription opioids, or past-month binge or heavy drinking. A diagnosis of an STI should prompt clinicians to screen for substance use, in particular, alcohol abuse/dependence and marijuana use.
Keywords: Adolescent; Adult; Child; Female; Health Surveys; Humans; Male; Prevalence; Self Report; Sexually Transmitted Diseases; Substance-Related Disorders; United States